2003
DOI: 10.1208/pt040467
|View full text |Cite
|
Sign up to set email alerts
|

Thermal porosity analysis of croscarmellose sodium and sodium starch glycolate by differential scanning calorimetry

Abstract: KEYWORDS: thermoporometry, differential scanning calorimetry (DSC), croscarmellose sodium (CCS), sodium starch glycolate (SSG) The aim of the study was to demonstrate the applicability of differential scanning calorimetry (DSC) on porosity analysis for cellulose and starch. Croscarmellose sodium (CCS) and sodium starch glycolate (SSG) were allowed to sorb moisture in 85%, 90%, 95%, and 100% relative humidity (RH) at 40°C for 24 hours. The pretreated samples were then subjected to DSC running temperature rangin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…Whereas, tablets packed in PVdC blisters showed prolonged disintegration time which may be due to the absorption of moisture during storage which decreases the efficiency of the disintegrant. F1 showed more prolonged disintegration time than that of F2 owing to the presence of croscarmellose sodium which have high tendency to adsorb more moisture than Explotab in F2 which is in agreement with Faroongsarng et al (38) who reported that croscarmellose sodium adsorb more than 400% of moisture upon storage at 6. Effect of ageing on the drug content of F2 stored under different stress conditions 85% RH while Explotab adsorb more than 300% of moisture if kept at same humidity level.…”
Section: Accelerated Stability Testingsupporting
confidence: 87%
“…Whereas, tablets packed in PVdC blisters showed prolonged disintegration time which may be due to the absorption of moisture during storage which decreases the efficiency of the disintegrant. F1 showed more prolonged disintegration time than that of F2 owing to the presence of croscarmellose sodium which have high tendency to adsorb more moisture than Explotab in F2 which is in agreement with Faroongsarng et al (38) who reported that croscarmellose sodium adsorb more than 400% of moisture upon storage at 6. Effect of ageing on the drug content of F2 stored under different stress conditions 85% RH while Explotab adsorb more than 300% of moisture if kept at same humidity level.…”
Section: Accelerated Stability Testingsupporting
confidence: 87%
“…Void space-sensitive methods use a fluid (gas or liquid) to directly access the pore volume in the sample. These techniques include helium pycnometry (see section 3), mercury porosimetry (see section 4), nitrogen adsorption (Ferrero and Jiménez-Castellanos, 2002;Westermarck et al, 1999;1998a) as well as thermoporometry (Faroongsarng and Peck, 2003;Iza et al, 2000;Luukkonen et al, 2001). Cost-effective and simple analysis using an oil absorption method has been reported for the measurement of the porosity of non-uniform ribbons from a roller compaction process (Khorasani et al, 2015a).…”
Section: Introductionmentioning
confidence: 99%
“…It has been suggested that freezing of the first few layers of water associated with a polymer cannot be detected by DSC analysis . Typically, it requires a few layers of water associated with the polymer and, with certain disintegrants, freezable water does not appear until the excipient is exposed to 95% relative humidity . The DSC thermograms for each particular grade of Polyplasdone ® eventually reveals an endotherm near 0°C when a mass of water greater than 100% of the mass of the polymer is associated with the polymer (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been suggested that water that has been internalized by being taken up into pores of the polymer sample would appear as freezable water and has the properties of bulk water . It is expected that water found in layers well removed from the polymer surface or internalized in pores would collectively be responsible for the broader second peak near 0°C in the thermograms.…”
Section: Discussionmentioning
confidence: 99%